Improvement of Working Conditions of Mining Workers by Reducing Nitrogen Oxide Emissions during Blasting Operations - Marat Rudakov; Ruslan Babkin; Ekaterina Medova (Applied Sciences, 2021)
The article presents comparison of the values of maximum permissible concentrations, revealed during the analysis of the national standards of Russia and Australia in the field of regulation of nitrogen oxides. The impact of poisoning of the workers of the quarry with nitrogen oxides after blasting operations are presented. A detailed review of studies of methods for reducing nitrogen oxide emissions is given. The way of decreasing emission of nitrogen oxides using highly active catalysts as a part of the profiled tamping is offered. Laboratory studies were carried out using a model explosive and pentaerythritol tetranitrate. The results obtained showed that zinc carbonate (ZnCO3) is the most effective. The reduction in the amount of nitrogen oxide emissions was 40% of that released during experiments without the addition of catalysts.